Low power CMOS iImage sensor for face recognition - Chan, Kit Heng; Ruslan, Siti Hawa (Penerbit UTHM, 2020)
Imaging system is suitable for different purposes, depending upon their final application. Digital cameras, camcorders, webcams, security cameras or infrared (IR) cameras are well-known imaging systems. For complementary metal oxide semiconductor (CMOS) image sensors, its performance is more promising compared to charged coupled device (CCD) due to its low power consumption, low cost, and on chip functionality and compatibility with standard CMOS technology [1]. In face recognition mode, three dimensional cameras replaced two-dimensional images to measure the object size, distance and shape with time-of-flight (TOF) cameras. Depth information can be extracted to be compared with database [2]. Therefore, CMOS image sensor with its architecture on pixel array, signal processors, row and column selector and timing control [3] will be the main key.